Development and Validation of the Elderly Suicide Screening Scale - Silva, Sabrina Piccinelli Zanchettin [UNESP]; Phinney, Alison; Rebustini, Flávio; Jamas, Milena Temer [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (Bentham Science Publishers, 2024)
Background: This study stems from the need to develop and validate a tool for interprofessional teams in Primary health care for screening for suicide among the elderly in the community. Objective: To evaluate the psychometric properties of the Non-Institutionalized Elderly Suicide Screening Scale (Escala de Rastreamento de Renúncia à Vida no Idoso não institucionalizado-ERRVI). Methods: This is a psychometric study focused on evaluating evidence of content validity and internal structure. The ERRVI construction process followed the guidelines for scale development based on theoretical models derived from qualitative research, which followed the methodological and theoretical approaches of grounded theory and symbolic interactionism. It is a theory called Symbolic Interactionism (Joel M. Charon). The instrument underwent content validity evidence analysis carried out by a panel of experts, considering the Content Validity Index (CVR). After the pre-test, the internal structure was evaluated using Exploratory Factor Analysis (AFE). Reliability was assessed using three indicators: Cronbach's alpha, Omega, and ORION scores. It involved 300 elderly individuals from two municipalities in the central-western region of Sao Paulo, Brazil, and was conducted from September to November 2020. Results: The final version comprised 31 items, categorized into four dimensions: autonomy, self-governance, self-care, and life satisfaction. The total explained variance was 50.82%, with factor loadings ranging from 0.31 to 0.86. The reliability indicators revealed a Cronbach’s alpha of 0.88, McDonald's Omega of 0.95, and scores for the dimensions assessed by the Overall Reliability of Fully-Informative Prior Oblique N-EAP (ORION) ranging from 0.78 to 0.84. Conclusion: The ERRVI showed evidence of content validity and internal structure in accordance with the recommended psychometric parameters. This is an innovative tool with the social value, given the scarcity of tools that screen the risk of suicide among the elderly in the community. It is the first of its kind in Brazil and the third globally.
Keywords: Aged; Autonomy; Behavior rating scale; Geriatric assessment; Primary health care; Public health; Self-governance; Suicide